Asymptomatic Clostridium difficile colonisation and onward transmission - Eyre, D; Griffiths, D; Vaughan, A; Golubchik, T; Acharya, M; O'Connor, L; Crook, D; Walker, A; Peto, T (Public Library of Science, 2013)
Combined genotyping/whole genome sequencing and epidemiological data suggest that in endemic settings only a minority of Clostridium difficile infection, CDI, is acquired from other cases. Asymptomatic patients are a potential source for many unexplained cases. Methods We prospectively screened a cohort of medical inpatients in a UK teaching hospital for asymptomatic C. difficile carriage using stool culture. Electronic and questionnaire data were used to determine risk factors for asymptomatic carriage by logistic regression. Carriage isolates were compared with all hospital/community CDI cases from the same geographic region, from 12 months before the study to 3 months after, using whole genome sequencing and hospital admission data, assessing particularly for evidence of onward transmission from asymptomatic cases. Results Of 227 participants recruited, 132 provided ≥1 stool samples for testing. 18 participants were culture-positive for C. difficile, 14/132(11%) on their first sample. Independent risk factors for asymptomatic carriage were patient reported loose/frequent stool (but not meeting CDI criteria of ≥3 unformed stools in 24 hours), previous overnight hospital stay within 6 months, and steroid/immunosuppressant medication in the last 6 months (all p≤0.02). Surprisingly antibiotic exposure in the last 6 months was independently associated with decreased risk of carriage (p = 0.005). The same risk factors were identified excluding participants reporting frequent/loose stool. 13/18(72%) asymptomatically colonised patients carried toxigenic strains from common disease-causing lineages found in cases. Several plausible transmission events to asymptomatic carriers were identified, but in this relatively small study no clear evidence of onward transmission from an asymptomatic case was seen. Conclusions Transmission events from any one asymptomatic carrier are likely to be relatively rare, but as asymptomatic carriage is common, it may still be an important source of CDI, which could be quantified in larger studies. Risk factors established for asymptomatic carriage may help identify patients for inclusion in such studies.